Valued Supply Chain for Integrated Hospital Management: A Conceptual Framework - Abu Raihan Bhuiyan Albarune; Nazma Farhat; Farzana Afzal (International Journal of Supply Chain Management, 2015)
Thispaperbasedonsecondarydata,therefore,theauthorsconstructedconceptualframeworkafterthoroughanalyzedanumerousresearchpapers.DuetoscarcitystudiesonServiceIndustrySupplyChainManagement(SCM),thispaperwouldcreateanobleapproachforthecurrenthealthcaremanagersofhospitalstoreviewandapprisetheiroperationalandstrategicalobjectives.ThisstudyhighlightSupplyChainManagement(SCM)conceptforthehospitalwhichrepresentingaserviceindustry.InadditionthisstudyrevealsthelimitedapplicationofSCMinhospital.Consequentlytheauthorsdescriberecommendationandproposesamodelonvaluedsupplychainmanagementinhospital.Thoughthispaperhighlightsinintensiveanalysis,however,itunlocksfurtherfrontiersfortheprospectiveresearchersaswellaspractitionersinordertodevelopSCMmodelforhospital.